An Approach to Reviewing Local Context for Exception from Informed Consent Trials Using a Single IRB. Issue 6 (9th November 2021) - Johnson, Ann R.; Rigtrup, Lisa M.; VanBuren, John; Rothwell, Erin; Dean, J. Michael
Abstract: In the context of emergency research, researchers can ask the institutional review board (IRB) to waive the regulatory requirement that individuals provide informed consent when enrolling in research studies. A requirement of the waiver of informed consent is that the reviewing IRB must review and approve a community consultation and public disclosure plan. It is critical that an IRB serving as the single IRB (sIRB) for multisite research be thoroughly versed in the local context concerns for each participating site to determine whether the site's community is being adequately consulted about the research in which individuals will be enrolled under an exception to the informed consent requirement. We designed an sIRB review model for evaluating site‐specific community consultation plans that included a local evaluation and feedback step, and we piloted the model with a four‐site, pediatric exception from informed consent (EFIC) clinical trial. We identified three key roles for the model: the sIRB, the investigators, and the representative of the institution's human research protection program (HRPP). We successfully collected the information and local input needed to evaluate each site's community consultation plan and applied the information to a thorough IRB review, despite the geographic distance between the study site and the sIRB.